2022
DOI: 10.2147/ijn.s372254
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Small Extracellular Vesicles: A Novel Approach for Kidney Disease Treatment

Abstract: Globally, kidney disease has become a serious health challenge, with approximately 10% of adults suffering with the disease, and increasing incidence and mortality rates every year. Small extracellular vesicles (sEVs) are 30 nm–100 nm sized nanovesicles released by cells into the extracellular matrix (ECM), which serve as mediators of intercellular communication. Depending on the cell origin, sEVs have different roles which depend on internal cargoes including, nucleic acids, proteins, and lipids. Mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 108 publications
0
15
0
1
Order By: Relevance
“…Besides soluble cytokines, EVs such as exosomes (30–100 nm in diameter) and microvesicles (100–1,000 nm in diameter) have been described as a different form of cell-to-cell communication through the horizontal transfer of microRNAs (miRNAs), mRNAs, and proteins-to-target cells ( Lu et al, 2022 ). Apart from the stem cells mentioned above, all regions of the nephron can release EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides soluble cytokines, EVs such as exosomes (30–100 nm in diameter) and microvesicles (100–1,000 nm in diameter) have been described as a different form of cell-to-cell communication through the horizontal transfer of microRNAs (miRNAs), mRNAs, and proteins-to-target cells ( Lu et al, 2022 ). Apart from the stem cells mentioned above, all regions of the nephron can release EVs.…”
Section: Discussionmentioning
confidence: 99%
“…73 Choi et al reported that kidney-derived MSC-EVs led to increased density and perfusion of renal capillaries through the downregulation of hypoxia inducible factor-1α. 74 Conversely, MSC-EVs produced by platelets or lymphocytes can also inhibit angiogenesis, mainly by increasing oxidative stress in target cells. MSC-EVs from lymphocytes can stimulate or inhibit angiogenesis depending on the conditions under which they are generated.…”
Section: Modulating Angiogenesismentioning
confidence: 99%
“…Choi et al. reported that kidney‐derived MSC‐EVs led to increased density and perfusion of renal capillaries through the downregulation of hypoxia inducible factor‐1α 74 …”
Section: Modulating Angiogenesismentioning
confidence: 99%
“…The regenerative potential of mesenchymal stem cells of different origins has been studied and contrasted by numerous research groups (40)(41)(42). The source from which organ-specific mesenchymal stem cells have traditionally been extracted is bone marrow.…”
Section: Introductionmentioning
confidence: 99%